2004
DOI: 10.1038/nmat1183
|View full text |Cite
|
Sign up to set email alerts
|

Flow-induced properties of nanotube-filled polymer materials

Abstract: Carbon nanotubes (CNTs) are under intense investigation in materials science owing to their potential for modifying the electrical conductivity sigma, shear viscosity eta, and other transport properties of polymeric materials. These particles are hybrids of filler and nanoscale additives because their lengths are macroscopic whereas their cross-sectional dimensions are closer to molecular scales. The combination of extended shape, rigidity and deformability allows CNTs to be mechanically dispersed in polymer m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

30
345
6

Year Published

2005
2005
2012
2012

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 437 publications
(385 citation statements)
references
References 39 publications
30
345
6
Order By: Relevance
“…The formation of extended networks of particles dispersed in a fluid gives rise to a discontinuous change in the rheological [1][2][3][4][5] and electrical [6][7][8][9] properties of the dispersion at concentrations around the so-called percolation threshold. Historically, percolation theory was first used by Flory [10] to explain the phenomenon of gelation in thermosetting polymers.…”
Section: Introductionmentioning
confidence: 99%
“…The formation of extended networks of particles dispersed in a fluid gives rise to a discontinuous change in the rheological [1][2][3][4][5] and electrical [6][7][8][9] properties of the dispersion at concentrations around the so-called percolation threshold. Historically, percolation theory was first used by Flory [10] to explain the phenomenon of gelation in thermosetting polymers.…”
Section: Introductionmentioning
confidence: 99%
“…It is also observed that the application of shear during melt-mixing promotes the breakdown of the 'aggregate' [10]. It is well established that 'network-like structure' [11,12] of CNT is predominantly responsible for electrical percolation in insulating polymer matrices. However, the electrical percolation threshold in polymer/CNT composites is found to be much higher in case of thermoplastic matrices [13,14] as compared to theoretically predicted percolation threshold considering L/D of CNT as one of the critical parameters which is otherwise found to be close to the predicted values in thermoset (epoxy, polyimide etc.)…”
Section: Introductionmentioning
confidence: 99%
“…This is manifested in much higher electrical percolation threshold in multiwall carbon nanotubes (MWNT) filled polyamide6 (PA6) composites [16,17]. Even if conductivity measurements during melt-state indicated a very low electrical percolation threshold (0.0025 < / < 0.01) in MWNT filled polypropylene (PP) composites [11], the room temperature measurement of PP/MWNT composites [14] showed higher electrical percolation threshold (1-2 wt%). These observations necessitate the retention of 'networklike structure' of MWNT in polymer matrix even after solidification, which can otherwise be observed in meltstate at low volume fraction of MWNT.…”
Section: Introductionmentioning
confidence: 99%
“…The viscoelastic properties of the PMMA nanocomposites containing SWNT, MWNT, CNF, or CB are presented in Figure 3 for a range of filler mass fractions. The storage modulus G' provides a measure of nanocomposite 'stiffness' and its frequency dependence characterizes whether the material is in a liquid-like or solid-like state 24 . At 200 ºC and low frequencies, the PMMA/CB composites have nearly the same rheological response as pure PMMA, regardless of the CB concentration, exhibiting the typical rheological response of a Newtonian liquid behavior with G'~ω 2 at low frequencies.…”
mentioning
confidence: 99%
“…However, for the composites containing a higher concentration of these extended fillers, this liquid-like low frequency scaling of G' disappeared and G' became nearly constant at low frequencies. This indicates a transition from a Newtonian liquid to an ideal Hookean solid, which accompanies the formation of a mechanically stable network structure 24,35 ('jammed network' or 'dispersion gel') 36 . We term the composition at which this rheological state is achieved the "gel concentration", φ g .…”
mentioning
confidence: 99%